Prevalence of Overweight and Associated Risk Factors in Primary School Children in Nilai, Negeri Sembilan - Yong, Kimberly, Wen Min; Ambusam, Subramaniam; Sivaguru, Muthusamy; Vinosh Kumar, Purushothaman (INTI International University, 2019)
Background: Childhood obesity is an alarming problem happening in this century where overweight children slowly becomes obese adult in the future if this phenomenon persist. There are many contributing factors towards childhood obesity but there are limited information regarding the prevalence and associated risk factors of overweight children in Nilai, Negeri Sembilan. Objective: 1. To determine the prevalence of overweight among primary school children aged 11 to 12 years in Nilai, Negeri Sembilan. 2. To examine the association between prevalence and the risk factors of overweight and obesity of primary school children aged 11 to 12 years in Nilai, Negeri Sembilan. Design: Cross-sectional study Methodology: A validated sociodemographic questionnaire, Physical Activity Questionnaire (PAQ-C) and Children Sleep Habit Questionnaire (CSHQ) was given to 118 primary school students. Descriptive statistics were used to tabulate the socio-demographics detail whereas chi-square were used to analyse the association between BMI and risk factors. Results: There is a prevalence of 6.8% of overweight children. Ethnicity, education level of the parents/guardian and the energy density (food consumption) shows a significant association with the children’s BMI level and waist circumference. Conclusion: Childhood obesity might be an alarming problem in the society with the choice of dietary and physical inactivity. An early awareness and education of good diet, appropriate sleep and importance of physical activity could prevent the increase of childhood obesity prevalence rate at the earliest.